(untitled) (gjstudies, 2020)
This research introduces a novel methodological framework for assessing financial statement comparability across international jurisdictions, employing a hybridapproach that integrates principles from computational linguistics, network theory,and institutional economics. While traditional comparability metrics have focusedprimarily on accounting standards harmonization, this study proposes a multidimensional comparability index (MDCI) that captures syntactic, semantic, andinstitutional dimensions of financial reporting. The methodology develops a corpusof financial statements from 500 multinational corporations across 15 jurisdictionsfrom 1995 to 2004, applying natural language processing techniques to extract andcompare disclosure patterns, measurement practices, and presentation formats. Akey innovation is the application of graph theory to map the relational structureswithin financial statements, enabling the quantification of structural comparability beyond content analysis. The research addresses the previously underexploredquestion of how non-accounting institutional factors—including legal systems, enforcement regimes, and cultural dimensions—interact with formal accounting standards to produce comparable financial information. Results demonstrate that formal accounting convergence explains only 38% of variance in actual comparability,with institutional complementarities accounting for an additional 42%. The studyreveals three distinct comparability clusters among jurisdictions that cut across traditional accounting families, challenging conventional classifications. Furthermore,the analysis identifies specific disclosure elements that contribute disproportionatelyto comparability from international investors’ perspectives, providing actionableinsights for standard-setters and regulators. The MDCI shows strong predictivepower for foreign investment flows, explaining 67% of variance in cross-border equity investments beyond traditional determinants. This research contributes to theinternational accounting literature by providing a more nuanced, computationallysophisticated approach to measuring comparability, while offering practical toolsfor investors navigating global capital markets